2022
DOI: 10.1007/s00344-022-10654-w
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Strigolactone (GR24) Positively Regulates Growth, Photosynthesis, and Improves Glandular Trichome Attributes for Enhanced Artemisinin Production in Artemisia annua

Abstract: Artemisia annua is a medicinal plant particularly known for the production of a sesquiterpene lactone artemisinin; a specialty metabolite known for its efficacy in the treatment of malaria by killing different strains of Plasmodium falciparum due to radicals released upon the cleavage of its endoperoxide motif. Considering these facts and the immense medicinal value of artemisinin, the enhancement of in planta production of artemisinin is highly desirabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 66 publications
2
15
0
Order By: Relevance
“…However, far fewer studies have been reported about SL effects on the outgrowth of axillary buds in ratoon rice. GR24, a synthetic SL analog, has been widely used to study multiple pathways by which SL affects various aspects of plant growth and development [ 18 , 19 , 20 , 24 ]. In this study, we observed that after treatment with GR24, SL significantly inhibits the ratoon rate ( Figure 1 A–D), indicating that SL is involved in the growth regulation of the middle and upper axillary buds of ratoon rice, and that its mechanism is similar to that of tiller regulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, far fewer studies have been reported about SL effects on the outgrowth of axillary buds in ratoon rice. GR24, a synthetic SL analog, has been widely used to study multiple pathways by which SL affects various aspects of plant growth and development [ 18 , 19 , 20 , 24 ]. In this study, we observed that after treatment with GR24, SL significantly inhibits the ratoon rate ( Figure 1 A–D), indicating that SL is involved in the growth regulation of the middle and upper axillary buds of ratoon rice, and that its mechanism is similar to that of tiller regulation.…”
Section: Discussionmentioning
confidence: 99%
“…GR24 application increased the activity and gene expression of antioxidant enzymes, and it reduced malonaldehyde (MDA) and hydrogen peroxide (H 2 O 2 ) content in Low Light stressed plants (LL-stressed plants) [44,45]. These results suggested that exogenous application of GR24 enhances plant tolerance to LL and improving photosynthesis by promoting utilization of light energy to alleviate photosystem injuries induced by excess light energy and ROS as well as enhancing photosynthesis efficiency to improve plant growth [45,46]. Exogenous GR24 application on tomato seedlings reduces the negative effects of low light exposure in at least three ways: by reducing growth inhibition, improving photosynthetic efficiency, and relieving oxidative stress [45,47,48].…”
Section: Impact On Low-light Stressmentioning
confidence: 94%
“…Carbonic anhydrase (CA) activity in fresh leaves was measured using the protocol developed by Wani et al. (2023) .…”
Section: Methodsmentioning
confidence: 99%
“…Carbonic anhydrase (CA) activity in fresh leaves was measured using the protocol developed by Wani et al (2023). Fresh leaf sample (0.2 g) devoid of veins were sliced into small rectangular pieces and submerged in 10 mL of 0.2 M aqueous cysteine hydrochloride solution.…”
Section: Carbonic Anhydrase (Ca) and Nitrate Reductase (Nr) Activitiesmentioning
confidence: 99%